Study on the Workspace and Structural Parameter of 3-RPS Parallel Robot - Pu Zhixin; Li Yanmei; Yu Yinghua (Jixie chuandong)
The three-dimensional model is built based on the structure characters of 3-RPS parallel robot through using Pro/E software.The inverse kinematics of the mechanism is obtained by using a new numerical algorithm,and the limit searching method is used to simulate the workspace through using MATLAB software.The simulation results are compared with the Euler angle algorithm.The influence of mechanism parameters on the workspace is analyzed,and the maximum volume of workspace in the parameter range is derived.A foundation for parallel robot parameter optimization and path planning is Laid.